Rancang Bangun Alat Monitoring Pulsa Listrik Rumah Tinggal Berbasis Raspberry Pi Dengan Notifikasi Sms Dan E-mail - Sherli Wahyuni Dwi Afriani; Ibnu Ziad; Suroso Suroso (STIKOM Tunas Bangsa Pematangsiantar, 2019)
In this design presents the design of electric pulse monitoring devices in residential homes. This tool is designed using the Raspberry Pi as a microprosessor. In the design process, this tool uses a light sensor (Light Dependent Resistor) to read the change of lights from green to red on the electric token, Camera Pi NoIR to take pictures of electric pulses, and SIM 800 to send SMS notifications. With the programming language used in the design of this tool is Language C. In monitoring the use of electric pulses, this tool is also designed to be able to send notifications automatically when the use of electric pulses has reached the minimum limit. Notifications sent will be received in the form of sms and email by the homeowner. It is expected that this tool can provide convenience to homeowners to monitor the use of electric pulses from a distance when the house is empty.